Pengaruh Citra Perusahaan, Kualitas Pelayanan, dan Electronic Word Of Mouth Terhadap Keputusan Pembelian Sepeda Motor Pada CV. Dunia Motor Jaya Kota Probolinggo - Iqbal Syah Bima, Ahmad; Haris, Abdul; Hermanto, Hermanto (Politeknik Negeri Jakarta, 2025)
The research aims to determine the effect of company image, service quality and electronic word of mouth partially on the decision purchase a motorcycle at CV. World Motor Jaya City of Probolinggo. The type of research used is a quantitative approach, with independent variables company image, service quality and electronic word of mouth and the dependent variable is purcashing decisions. The population in this research is consumers exist in january month 2025, which is not yet known for certain, the sampling technique used is non-probability sampling of 100 samples. The data sources used in this research come from primary data and secondary data, with the help of the Smart-PLS 4 application. The research results show that the company image variable (X1) has a positive and significant effect on purchasing decision (Y). The service quality variable (X2) has a positive and significant effect on purchasing decision (Y). The electronic word of mouth variable (X3) has a positive and significant effect on purchasing decision (Y).